Do user-generated content and micro-celebrity posts encourage generation Z users to search online shopping behavior on social networking sites—the moderating role of sponsored ads - Sabakun Naher Shetu (Future Business Journal)
Abstract The study investigates the impact of user-generated content (UGC) and micro-celebrity posts on the online purchasing behavior of Generation Z on social networking sites. In addition, the mediator function of the user’s search intent is investigated. Thus, sponsored ads employ moderation. To collect primary data, self-administered questionnaires and cross sectional studies were applied. The population is comprised of university students of Generation Z from Dhaka, Bangladesh. Systematic random sampling was used to select Generation Z members from six institutions in the city of Dhaka. Using convenience sampling, primary data were collected. The research yielded 565 standardized questionnaire samples. The study’s findings demonstrated that user-generated content’s direct, indirect, and mediation relationships were statistically significant. Moreover, the direct and indirect relationships of micro-celebrity posts were found to be statistically significant, but the mediation relationship was found to be insignificant. Additionally, users’ search intention has a strong correlation with online purchasing behavior. Thus, the moderation analysis of sponsored ads was deemed crucial. In Bangladesh, the stimulus-organism-response (S-O-R) paradigm is rarely applied to studies on the online purchasing preferences of Generation Z consumers. This study also examined its findings’ implications for future research and limitations.